F-fluorodeoxyglucose-positive emission tomography/CT imaging for left ventricular assist device-associated infections in children. (20th July 2018) - Absi, Mohammed; Bocchini, Claire; Price, Jack F.; Adachi, Iki
Abstract: Left ventricular assist device implantation is an important therapeutic option for children with end-stage heart failure. However, device-related complications such as infection may occur while the patient is supported. Device-associated infection can be life-threatening, and early detection is critical. F-fluorodeoxyglucose positron emission tomography and CT is a highly sensitive imaging modality for the detection of an inflammatory response and is useful to evaluate the response to antibiotic therapy. We present two case reports of a left ventricular assist device-associated infection detected by F-fluorodeoxyglucose positron emission tomography and CT in children.